2016
DOI: 10.1371/journal.pone.0162285
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns and Practices and Birth Weight in Northern Ghana

Abstract: BackgroundAdequate maternal nutrition is a key factor for achieving good pregnancy outcomes. Moreover, inadequate dietary intake during pregnancy is considered an important contributor to maternal malnutrition in developing countries. Although some studies have examined the effect of the entire diet on birth outcome, most studies have been very narrow because they considered the effect of single nutrient. The single nutrient approach is a major setback because usually several nutrient deficiencies are more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
88
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 41 publications
16
88
3
2
Order By: Relevance
“…Excess birth weight in this study could be explained by maternal anthropometry before and during pregnancy as well as gestational weight gain. In addition, several studies have shown that excess birth weight is primarily associated with excess maternal weight before pregnancy, excess gestational weight gain, gestational diabetes and multiparity [11,37,38]. This could be consistent with the characteristics of women in this study with the exception of gestational diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Excess birth weight in this study could be explained by maternal anthropometry before and during pregnancy as well as gestational weight gain. In addition, several studies have shown that excess birth weight is primarily associated with excess maternal weight before pregnancy, excess gestational weight gain, gestational diabetes and multiparity [11,37,38]. This could be consistent with the characteristics of women in this study with the exception of gestational diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate 7.6% and 5.5% respectively of LBW and excess birth weight. Similar results have been reported in other countries in Africa within the same population type [11,13,28].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations